Kebijakan Pemerintah Daerah Kabupaten Malang dalam Pengembangan Industri Pariwisata - Setyanto, Tri Joko; Andin Rusmini (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2023)
Malang Regency is one of the largest regencies in East Java that has unique and diverse tourism potential. Although the tourism potential is large, tourist visits are still not optimal. This is due to the lack of knowledge and understanding of tourists about Malang's tourism potential. The purpose of the research is to find out the strategies and policies of the Malang Regency Government in developing the tourism industry. The research method used is normative legal research with a statutory approach and conceptual approach. The results show that the Malang Regency Government has implemented a number of policies to develop the tourism industry. These policies include the establishment of the Tourism and Culture Office, branding "Malang Regency: The Heart of East Java," promotion through several events, the formation of Sub-district Tourism Partners, and the preparation of the regency tourism development master plan.